Emotional Well-Being and Traditional Cypriot Easter Games: A Qualitative Analysis - Koundourou, Christiana; Ioannou, Markella; Stephanou, Chara; Paparistodemou, Maria; Katsigari, Theodora; Tsitsas, Georgios; Sotiropoulou, Kyriaki (Frontiers in Psychology, 2021)
The aim of the current study is to examine the effect of the Traditional Easter Games of Cyprus on the emotional well-being of the participants. Data were collected using a mixed method analysis. It consisted of interviews from 51 participants aged 32-93 years old, and observations made from audiovisual material of the Traditional Cypriot Easter Games being played with a sample of 20 children aged 6-14 years old and 43 adults aged 18-65 years old. From the interviews demographic data were collected and analyzed using IBM SPSS program. The observations of the audiovisual material focused on the emotions of the participants and were grouped based on their frequency and duration into prevailing and secondary emotions. The results indicate that the games produce emotions such as joy, excitement and euphoria. Emotions such as embarrassment, frustration and anger were also observed occasionally, specifically in situations of competitiveness and defeat. In addition, the differences and similarities between adults and children were recorded. The findings of the present study extend previous work by demonstrating the positive impact of the traditional games on the emotional well-being.